Non-financial incentives for the post-90s employees: case of Hunan Education Publishing House - YAN, HAN (2017)
Post-90s employee is a special group of people in organizations. According to a bureau of statistics of China in 2015, there were 211 million post-90s in China, which made up 15.4% of the total population in China, so that post-90s will be the driving force of China’s development in the future. Meanwhile, Hunan Education Publishing House is a famous publisher in China. Therefore, this dissertation will look post-90s employees in Hunan Education Publishing House as the research objects.